(untitled) (Anclajes, 2018)
After founding literary journals, co-directing the cultural supplement of a large daily newspaper, and collaborating in various publications, Jorge Luis Borges and Adolfo Bioy Casares founded the editorial Destiempo in 1937. This article hypothesizes that in the same way in which Borges returned to his texts to rewrite them, in Destiempo he went back to reedit previously edited texts. This analysis deals with the main characteristics of this editorial project and identifying relevant editorial decisions.